Relationships between psychological abuse, cognitive-emotional regulation strategies, social self-efficacy and internalizing-externalizing behavioral problems among adolescents in Fars, Iran - Momtaz, Vahid (2016)
Adolescent behavioral problems are serious public health issues. It is reported that the prevalence of behavioral problem among Iranian adolescents in the age group 12 to 19 years old is the highest compared to other age groups. This showed that adolescents are at-risk populations for behavioral problems. Therefore, this study was designed to investigate the relationships between psychological abuse, cognitive emotional regulation strategies, social self-efficacy with behavioral problems (internalizing and externalizing), and the moderating roles of cognitive emotional regulation strategies and social self-efficacy on the relationships between psychological abuse with internalizing and externalizing behavior problems among the adolescents of Fars Province, Iran. The present study employed developmental psychopathology approach of Rutter and Sroufe, Ecological-Transactional Theory of Cicchetti and Toth, Bandura‟s Social Cognitive Theory, and Self-Regulation Theory in providing a valid basis for explaining and predicting externalizing and externalizing behavior problems among the adolescents of Fars Province, Iran. Simple random sampling method was used to recruit a total of 328 adolescents aged 12 to 19 years from psychological clinics of Shiraz, Iran. This study is a quantitative research with correlational research design. The respondents completed the Youth Self-Report (Achenbach, 1991), Psychological Abuse (Momtaz, Mariani, Mansor, & Rojanah, 2013), Cognitive Emotion Regulation Questionnaire (Garnefski, Kraaij, & Spinhoven, 2002), and Adolescent Social Self-Efficacy Scale (Connolly, 1989). Structural equation modeling indicated that adolescents with psychological abuse, negative cognitive emotional regulation strategies, low levels of positive cognitive emotional strategies, and low levels of social self-efficacy were more likely to report behavior problems. Social self-efficacy and cognitive emotional regulation strategies moderated the relationship between psychological abuse and behavior problems. These variables explained 49.0% of the variance in internalizing behavior and 30.0% in externalizing behavior. The present study increases the understanding on the importance of psychological abuse and negative cognitive emotional regulation strategies as the risk factors, and social self-efficacy and positive cognitive emotional regulation strategies as the protective factors against internalizing and externalizing behavior problems. The findings of the present study can be useful for therapists, parents, students, counsellors, and policy makers.